Possibilities of Applying the Principles of Data-Driven Decision-Making in Enterprises - Gabriel KOMAN; Ivana GABRIŠOVÁ (Communications of International Proceedings, 2024)
The effective use of data, information, and appropriate technical and software equipment is a hot topic with a growing impact on business success. Decision-making influenced by different aspects, highlighting the effect of suitable available information collected via information and communication technology, is an integral part of managerial work. Data-driven decision-making has, therefore, become a need rather than a simple competitive advantage. This paper contributes to the existing literature by urging organizations to adopt a data-driven approach to decision-making and helping them overcome implementation-related challenges. A qualitative content analysis of secondary data focused on four case studies was used to gain necessary insights. The case studies were chosen according to three parameters: (1) the central theme, (2) the publication date and (3) the use of primary research methods. The findings indicate that implementing data-driven decision-making in enterprises has several benefits, including increased supply chain efficiency, communication flows, and customer loyalty. Better data transfers also appeal to reduced decision-making time and improved customer relationships. However, inadequate data, subpar external sources, and limited internal resources greatly diminish the potential for data exploitation. This insight highlights how crucial it is for companies to create a data-centric culture and engage in strategic planning and training to overcome these obstacles.
Keywords: Information Technology. Management. Decision-making process. Data-driven decision-making.